Marine Seismic Tomography for Detecting Fracture and Void of Subsurface Seabed : a Theoretical Framework Development and Application of Wide-Band Fresnel Tomography - Bagus E. B. Nurhandoko; Fajril Ambia; Kaswandhi Triyoso; M. Thurisina Choliq; Mahatman L. Budi; Asep Suhendi; Wahyu E. Abdianto (Indonesian Journal of Physics, 2008)
Fracture as well as void can generate unstable structure in offshore building. We use seismic tomography based on scattering wave instead of conventional raypath seismic tomography. Conventional raypath tomography usually needs dense source-receiver configuration as well as wide-angle measurement. Therefore, it will be high cost in field data acquisition. We propose scattering wavepath tomography by means of Fresnel interpolated wavepath (FIW) wide-band inversion. FIW is an interpolation between imaginary part of Rhytov scattering wavepath and raypath. Then, FIW is combined with wide band inversion procedure to handle sparseness configuration of measurement. By this method, smooth constraint is implemented more naturally by based on wave's spectrum. In this paper, we showed some applications of Wide-band inversion of FIW tomography in imaging fracture and void in marine carbonate sea bed.